Factors affecting consumers’ behavior toward using medicinal plants - Ali Al-Saadi, Mahmood Al-Samydai, Ali AL-Samydai, Maha N. Abu Hajleh, Rudaina Othman Yousif, Dima Musa Al-Dajani, Lidia Kamal Al-Halaseh, Fatimah Akram Othman, Aburjai Ahmed (Journal of Applied Pharmaceutical Science, 2024)
Traditional medicinal practices relying on herbal remedies are prevalent in developing nations. Despite their extensive use, concerns persist regarding the lack of knowledge and perception associated with herbal therapy. This study aims to identify the factors influencing consumers’ behaviour toward the use of medicinal plants in treatment. An analytical descriptive approach was employed to elucidate consumers’ responses to the study variables and assess the impact of factors on their behaviour. The study focused on consumers of medicinal plants, with a sample size of 550 participants. The analyzed data unveiled a significant impact (α = 0.05) for four key variables: quality, trust, reference groups, and culture, influencing consumers’ behaviour regarding the use of medicinal plants. Product availability and cost emerged as additional considerations. The cultural dimension took precedence in consumers’ priorities, followed by trust, reference groups, quality, availability, and concluding with price. Overall, consumers in the study expressed positive assessments across all dimensions, reflecting a high level of satisfaction from their perspective. Measuring knowledge and assessing consumers’ attitudes toward using medicinal plants are crucial steps in understanding the factors influencing their behaviour in utilizing herbal medications. This understanding can inform strategies to enhance consumer engagement and promote informed decisions regarding herbal therapy.
Keywords: Consumer behavior, culture, medicinal plants, quality, reference groups